Hambatan Guru dalam Pengajuan Soal Literasi Matematika Bertema Word Problem - Syafrudin, Tomy; Vitantri, Ciptianingsari Ayu (Jurnal Tadris Matematika, 2024)
Teachers play a crucial role in developing students' mathematical literacy skills. One way teachers can assess their mathematical literacy skills is by how they pose questions with a word problem theme. Word problem questions are mathematical problems that occur in everyday life and are presented in narrative form. However, in reality, mathematics teachers often give questions in the form of mathematical symbols. This study aims to explore the obstacles experienced by teachers in compiling word problem mathematical literacy questions and their solutions. The method used is descriptive qualitative, with data collection techniques using tests and interviews. The data is then analyzed with the stages of reduction, data presentation, and conclusion. The subjects in this study were teachers from seven different schools in Jombang Regency. The results of the study showed that the obstacles for teachers in submitting mathematical literacy questions were: difficulty in developing interesting and relevant questions to real life, difficulty in developing HOTS questions, lack of evaluation in the process of compiling mathematical literacy questions, time constraints, lack of familiarity with interactive technology and lack of training in compiling mathematical literacy questions. The solutions offered: providing mathematical literacy training through discussions and workshops, encouraging teachers to collaborate and share question ideas with other teachers, and providing relevant technology training.